Analysis of the Influence of Blog Content on Brand Awareness in the Digital Age: A Case Study 99.co Indonesia - Tiara Syahra Syabani; Adhi Prasetyo (PT Mattawang Mediatama Solution, 2024)
In today's digital era, property search has changed to be easier and more efficient with the presence of the internet and online platforms. Property sites in Indonesia that are present in Indonesia have utilized e-marketing strategies to increase brand awareness. However, 99.co face challenges in building strong brand awareness. This study aims to investigate the effect of blog use on brand awareness 99.co Indonesia by examining credibility, believeable, unbiased, and trustworthy variables. This study used a quantitative approach with a sample of 400 respondents selected by accidental sampling. Data were collected through an online questionnaire and analyzed using linear regression. The results showed that the credibility, believeable, unbiased, and trustworthy variables of blogs significantly affected brand awareness. Trustworthy has the strongest influence followed by unbiased, credibility, and believeable. These findings provide insights for 99.co and similar platforms to continuously improve the quality of their blog content to strengthen brand awareness in a competitive market.